Kepemimpinan Digital sebagai Kunci Adaptasi Karyawan di Tengah Transformasi Teknologi - Netti Syafitri; Mulyadi, Mulyadi; Dewi Permata Sari; Sumardin, Sumardin; Sabri, Sabri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The rapid advancement of digital technology compels organizations to transform their leadership styles, operational systems, and organizational structures. In this context, employee adaptability emerges as a critical factor in ensuring organizational resilience and sustained performance. This study aims to examine the influence of Digital Leadership, Technological Transformation, and Organizational Change on Employee Adaptability. A quantitative approach was employed using a structured survey method, with data collected from 120 respondents working in a digitally integrated organization. Multiple linear regression analysis was performed using SPSS to test the hypotheses. The findings reveal that each independent variable (digital leadership, technological transformation, and organizational change) has a significant and positive effect on employee adaptability, both individually and collectively. Visionary and empowering digital leadership encourages employees to respond more effectively to change. Technological transformation enhances work flexibility and accelerates learning processes. Organizational change, when supported by leadership and internal readiness, strengthens employees’ adaptive capacity in facing uncertainty. This study concludes that the integration of leadership, digital systems, and organizational change is essential to fostering adaptability among employees. The results highlight the importance of a holistic strategy in developing a workforce that is resilient, responsive, and capable of thriving in an era of ongoing digital disruption.